Construction of heterojuncted photocatalyst with TiO2 quantum dots and graphene oxide nanosheets for highly efficient photocatalysis. (1st July 2021) - Wang, Guojing; Wang, Fengqi; Liu, Shuo; Li, Mingyang; Xie, Mingzheng; Yang, Zhilong; Xiang, Yunjie; Lv, Shasha; Han, Weihua
Abstract: To overcome the recombination issue of photocarriers, TiO2 quantum dots (QDs, nanoparticles in a few nanometers) were used to form heterojunctions with graphene oxide nanosheets. This combination has significantly enhanced the photocatalytic activity by providing more active reaction sites at the nanoscale surface and suppressing photocarrier recombination through fast separating the photocarriers by the internal electric field in the TO2 /graphene oxide heterojunctions. The enhancement in photocatalytic activity has been evidenced by the improved hydrogen generation rate in photoelectrochemical water splitting, which is about 30% higher than that of bare TiO2 QDs in the same situation. Moreover, the TiO2 /graphene oxide composite exhibits a lower flat band potential, which means a higher reducing potential of photo-excited electrons. Graphical abstract: The combination, TiO2 quantum dots with graphene oxide nanosheets, has significantly enhanced the photocatalytic activity by providing more active reaction sites at the nanoscale surface and suppressing photocarrier recombination through fast separating the photocarriers by the internal electric field in the TiO2 /graphene oxide heterojunctions. Image, graphical abstract